Middle sentences: An argument for conceptual structure - Estudillo Díaz, Luis Manuel (Pragmalingüística, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]--> Middle sentences in English are only partly described within the Government and Binding theory. Some semantic and discourse generalizations which are integral to the meaning of these constructions are just set aside, if they are mentioned at all. The theory of conceptual semantics developed by Ray Jackendoff (1983, 1987, 1990) presents the first viable alternative to the syntactic strategies descending from Chomsky’s theory. In this paper I will examine the middle voice and show how several Government and Binding analyses of these constructions fail to account for important parts of the data. I hope to persuade the reader that a conceptual structure analysis of this phenomenon provides a more appealing solution which fully integrates the syntactic and semantic generalizations.